Effect of Reality Therapy on Aggressive Behaviour of School Adolescents in Ife East Local Government, Ile-Ife, Osun State, Nigeria - Michael Adeniyi Omoyemiju (Indonesian Journal of Elementary Teachers Education, 2023)
The study determined the prevalence of aggressive behaviour among secondary school students in Ife-East Local Government Area and examined the effect of reality therapy in reducing aggressive behaviour. The study employed pre-test post-test control group designs. The study population comprised 1,515 senior secondary school students two (SSS II). A total of 398 students were selected using a multistage sampling procedure. Only 80 (5.3%) students that manifested severe level of aggressive behaviour from the analysis of the first phase and who were willing to participate in the counselling treatment were randomly assigned into experimental and control groups. An instrument titled “The aggressive Behavior Scale (ABS) was used to collect data for the study. Data collected were analysed using frequency counts, percentages and Analysis of Covariance. The results showed that 31.7% of the participants manifested severe aggressive behaviour while 51.8% and 16.5% exhibited moderate and mild aggressive behaviour respectively. The results showed a significant effect of reality therapy [F (1, 158) = 7.153, p-value = 0.008 0.05] on aggressive behaviour among students. The study concluded that aggressive behaviour was prevalent among secondary school students in Ife-East Local Government Area and that reality therapy was an effective treatment in the reduction of aggressive behaviour among secondary school students.